Accelerated hydrolysis of substituted cellulose for potential biofuel production: Kinetic study and modeling. (November 2015) - Mu, Bingnan; Xu, Helan; Yang, Yiqi
Graphical abstract: Highlights: Substitution greatly accelerated cellulose hydrolysis for bioethanol production. Kinetics of multi-stage hydrolysis of substituted cellulose was studied. Relationship between hydrolysis rate and critical kinetic parameters was built. Substitution and hydrolysis only occurred in amorphous regions of cellulose fibers. Abstract: In this work, kinetics of substitution accelerated cellulose hydrolysis with multiple reaction stages was investigated to lay foundation for mechanism study and molecular design of substituting compounds. High-efficiency hydrolysis of cellulose is critical for cellulose-based bioethanol production. It is known that, substitution could substantially decrease activation energy and increase reaction rate of acidic hydrolysis of glycosidic bonds in cellulose. However, reaction kinetics and mechanism of the accelerated hydrolysis were not fully revealed. In this research, it was proved that substitution therefore accelerated hydrolysis only occurred in amorphous regions of cellulose fibers, and was a process with multiple reaction stages. With molar ratio of substitution less than 1%, the overall hydrolysis rate could be increased for around 10 times. We also quantified the relationship between the hydrolysis rate of individual reaction stage and its major influences, including molar ratio of substitution, activation energy of acidic hydrolysis, pH and temperature.